2021
DOI: 10.24880/maeuvfd.922106
|View full text |Cite
|
Sign up to set email alerts
|

The role of resveratrol in hepatotoxicity caused by methotrexate

Abstract: Methotrexate is an immunosuppressive and antineoplastic drug that may induce hepatotoxicity. Resveratrol is a compound that has a protective effect thanks to its antioxidant role. In present study was aimed to investigate posibble protective effects of resveratrol in methotrexate induced hepatotoxicity. Eighteen Wistar Albino rats were equally divided into three groups: Control, Methotrexate, Methotrexate + Resveratrol. After a single dose of methotrexate (15 mg/kg, i.p.), resveratrol (10 mg/kg, orally) was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…showed that MTX-induced liver, kidney and heart damage was ameliorated with a flavonoid derivative diosmin (47) . Similar to these studies, there are studies in which vitamin C (7) , resveratrol (44) , quercetin (45) , berberine (48) and gallic acid (43) were used to treat MTX-induced tissue damage. In this study, whey proteins, which are known to have antioxidant properties, ameliorated MTX-induced oxidative damage by decreasing MDA level and increasing GSH level, SOD and GST activities.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…showed that MTX-induced liver, kidney and heart damage was ameliorated with a flavonoid derivative diosmin (47) . Similar to these studies, there are studies in which vitamin C (7) , resveratrol (44) , quercetin (45) , berberine (48) and gallic acid (43) were used to treat MTX-induced tissue damage. In this study, whey proteins, which are known to have antioxidant properties, ameliorated MTX-induced oxidative damage by decreasing MDA level and increasing GSH level, SOD and GST activities.…”
Section: Discussionmentioning
confidence: 94%
“…Since MTX induces oxidative stress by increasing reactive oxygen species in tissues (38,40,43) , the effects of various antioxidant substances against MTX-induced oxidative stress have been investigated (7,38,(43)(44)(45) .…”
Section: Discussionmentioning
confidence: 99%
“…Başka çalışmalarda da farklı doz ve sürelerde Mtx uygulamasının doku MDA düzeylerinde artışa yol açtığı gösterilmiştir (22,(25)(26)(27). Ayrıca Mtx karaciğer dokusunda oksidatif stres göstergelerinden olan TOS'ta da artışa neden olabilir (19,28). Çalışmamızda da MtxG'nin MDA ve istatistiksel anlamlı olmasa da TOS seviyelerinde literatürle uyumlu artış mevcuttu.…”
Section: Discussionunclassified
“…Mtx metaboliti olan Mtx-poliglutamatlar (Mtx-PGs), oksidan seviyelerini artırmalarının yanında, antioksidanları da baskılayarak karaciğer dokusunda oksidatif stresi indükleyebilir (29). Mtx uygulamasının; SOD, CAT ve GPx gibi antioksidan enzimlerde ve GSH'de azalmaya yol açtığı farklı çalışmalarda gösterilmiştir (27,30) İlave olarak Mtx TAS'ta da azalmaya neden olabilir (28). Biz de çalışmamızda literatürle uyumlu olarak MtxG'deki TAS, CAT ve SOD düzeylerinde, istatistiksel olarak anlamlı olmamakla birlikte bir düşüş saptadık.…”
Section: Discussionunclassified